Are Low Intakes and Deficiencies in Iron, Vitamin A, Zinc, and Iodine of Public Health Concern in Ethiopian, Kenyan, Nigerian, and South African Children and Adolescents?. Issue 3 (September 2017) - Harika, Rajwinder; Faber, Mieke; Samuel, Folake; Mulugeta, Afework; Kimiywe, Judith; Eilander, Ans
Objective: To perform a systematic review to evaluate iron, vitamin A, zinc, and iodine status and intakes in children and adolescents (0-19 years) in Ethiopia, Kenya, Nigeria, and South Africa. Method: Both national and subnational data published from the year 2005 to 2015 were searched via MEDLINE, Scopus, and national public health websites. For each micronutrient and country, status data from relevant studies and surveys were combined into an average prevalence and weighted by sample size (WAVG). Inadequate intakes were estimated from mean (SD) intakes. Results: This review included 55 surveys and studies, 17 from Ethiopia, 11 from Kenya, 12 from Nigeria, and 16 from South Africa. The WAVG prevalence of anemia ranged from 25% to 53%, iron deficiency from 12% to 29%, vitamin A deficiency (VAD) from 14% to 42%, zinc deficiency from 32% to 63%, and iodine deficiency from 15% to 86% in children aged 0 to 19 years from 4 countries. Generally, children <5 years had higher prevalence of anemia (32%-63%), VAD (15%-35%), and zinc deficiency (35%-63%) compared to children aged 5 to 19 years. Studies with intake data indicated that inadequate intakes ranged from 51% to 99% for zinc, 13% to 100% for iron, and 1% to 100% for vitamin A. Households failing to consume adequately iodized (>15 ppm) salt ranged from 2% in Kenya to 96% in Ethiopia. Conclusion: With large variation within the 4 African countries, our data indicate that anemia and vitamin A, zinc, and iodine deficiencies are problems of public health significance. Effective public health strategies such as dietary diversification and food fortification are needed to improve micronutrient intake in both younger and older children.